Knowledge, attitude and perception of tuberculosis management among tuberculosis-infected patients in resource constraint setting: field experience from Oyo state, South-West, Nigeria - Oladimeji, Olanrewaju; Tsoka-Gwegweni, Joyce Mahlako; Adeyinka, Daniel Adedayo; Makola, Lehlogonolo; Mitonga, Kabwebwe Honoré; Udoh, Ekerette Emmanuel; Hazangwe, Patrick (International Journal Of Community Medicine And Public Health, 2018)
Background: Inadequate knowledge and misconceptions about tuberculosis (TB) contribute to the burden of the disease by influencing patients’ behavior and attitude towards the disease and undermining infection control efforts. This study assesses the level of knowledge, attitude and perception of TB and its management among TB-infected patients. Methods: A descriptive cross-sectional was used to interview 712 TB patients using a semi-structured questionnaire between June and October 2016. Bivariate and multivariate analyses were performed with SPSS version 20. Results: About 70% had a good knowledge of TB. Patients’ perception of stigma was high (37.5%). A high proportion of the patients had a poor perception of their illness (88%). Healthcare workers attitude was rated as satisfactory by 97.2% of respondents. Patients who had good knowledge about TB experienced high self-stigma (42%) compared to those who had poor knowledge (27.2%), p<0.05. Poor knowledge of TB was highest among relapse TB cases. Respondents with poor TB knowledge were less likely to be male (OR: 0.66; 95% CI: 0.46, 0.95), married (OR: 0.24; 95% CI: 0.10, 0.55; p=0.001) and have tertiary education (OR: 0.06; CI: 0.37, 0.87; p=0.010). Patients with good knowledge about HIV and in the richest wealth status were 91% less likely to have high perceived stigma (OR: 0.09, 95%CI: 0.02, 0.35; p=0.001). Conclusions: The level of knowledge of TB among patients is satisfactory, however perception of illness is poor. Tuberculosis diagnosis can create self-stigma because of the fear of being isolated and discriminated which may determine the success of treatment.